A BIOLOGICAL-PSYCHOLOGICAL VIEW ON AGEING - Anton Coenen (Faculty of Psychology, Atma Jaya Catholic University of Indonesia, 2013)
In this paper two major views on ageing: the ‘genetic’ (‘programmed’) types of theories and the ‘wear-and-tear’ (‘damage’ or ‘error’) theories are presented. The genetic theories, saying that specific genes regulate ageing, explain the species differences better, while the wear-and-tear theories, implying that damages in the genome lead to ageing, explain the male-female differences better. The ‘survival curve’ (human’s survival as a function of time), shows that the maximum age is fixed, but that the average age still increases. Good food, a safe hygienic environment and adequate medical care play a positive role in human longevity. Notwithstanding that it can be stated that ageing is associated with somatic and, in particular, with cognitive decline. Brain degeneration as expressed in the diseases of Alzheimer and Parkinson are rather typical ageing disorders. However, natural ageing is also accompanied by mental and physical decline, presumably due to brain cell loss and loss of contacts between nerve cells. Presently, it becomes more and more clear that the decline due to ageing can be delayed or slowed down to a certain degree. Keeping the body and the brain active might be associated by a reduction in the loss of synapses, or even in the formation of extra synapses. This forms a compensation buffer for the decrease of general bodily processes, including cognitive functions. Especially, elderly people complain about memory problems. The memory decline is particularly in episodic memory. However, the procedural memory (for the performance of complex activities and skills) does not decline and the semantic memory (the memory concerned with meanings and concepts) even sometimes profits of the rise in age. Though old people have episodic memory problems, they have compensating types of memory, which delivers them to have an adequate response to life situations. This can be regarded as an increase in wisdom